Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Step-by-step explanation:
We know that
a=1 and b= -2
{3*1-4*(-2)+2} .{5*1+6}
= (13-11)
=2
Answer:
143
Step-by-step explanation:
(3a – 4b + 2) × (5a + 6)
a = 1 ; b = - 2
(3(1) – 4(-2) + 2) × (5(1) + 6)
Inputting the values of a and b
(3 - (-8) + 2) * (5 + 6)
(3 + 8 + 2) * (11)
13 * 11
= 143
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.